2020
DOI: 10.2166/wst.2020.376
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical approach towards adsorptive removal of Alizarin Red S dye using native chitosan and its successively modified versions

Abstract: In the present work, native chitosan (Ch) along with its chemically and physico-chemically modified versions namely sulphate cross-linked chitosan (SCC) and sulphate cross-linked chitosan-bentonite composite (SCC-B) were employed as potential adsorbents for the removal of an anionic dye, Alizarin red S (ARS) from aqueous solutions. All the three adsorbents were extensively characterized using techniques such as FT-IR, SEM, EDX, XRD, BET, TGA-DTA and pHPZC. Various parameters were optimized including pH of dye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…However, the combination of the two led to a much effective adsorption owing to the enhanced surface area of charcoal and the effective molecular interactions of chitosan. Similar results were reported by Khapre et al (2020) for successively modified materials towards alizarin red S dye.…”
Section: Materials Advances Papersupporting
confidence: 90%
See 1 more Smart Citation
“…However, the combination of the two led to a much effective adsorption owing to the enhanced surface area of charcoal and the effective molecular interactions of chitosan. Similar results were reported by Khapre et al (2020) for successively modified materials towards alizarin red S dye.…”
Section: Materials Advances Papersupporting
confidence: 90%
“…25 Several studies have been carried out on the adsorption of water pollutants using chitosan-activated charcoal composites involving the removal of dyes in the recent years. [26][27][28] Recently, we reported a composite of cellulose fabricated by the co-precipitation of Fe and Al in the cellulose material for the detoxification of various reactive dyes with high adsorption capacities. 29 In this study, we used a hybrid approach involving crosslinking chitosan with sodium tripolyphosphate (STTP) for imprioved mechanical strength and for entrapping activated carbon through the enhanced surface area and porosity, leading to a supersorbent with excellent confiscation capability for RBBR dye.…”
Section: Introductionmentioning
confidence: 99%
“…The values of q D are 184. 42 Au-NPs loaded on activated carbon 123.45 [48] Carbon nanotubes 135.2 [49] Activated carbon 20 [39] Iron oxide-modified activated clay 32.70 [50] Activated carbon 0.064 [51] Fe-BTC MOF 79.88 [52] Native chitosan 131.58 [53] FeWO 4 /PPy nanocomposite 142.80 Present study…”
Section: Freundlich Isotherm (Equation 7 In Tablementioning
confidence: 89%
“…1 Biosorption studies using a natural polymer in its native or modified state are gaining more importance nowadays. A number of naturally occurring polymers that are abundantly available in nature and upon proper treatment have been reported as effective adsorbents are cellulose, 2-4 chitin 5,6 and chitosan, [7][8][9][10][11] alginates, 12,13 clays, 14 magnetic ferrites 15,16 and resins. 17,18 They are applied for the removal of various water pollutants such as heavy metals, 19,20 dyes in single 21,22 and binary systems, 23 pesticides, paints etc.…”
Section: Introductionmentioning
confidence: 99%
“…Many workers have reported similar kinds of composites for the efficient removal of fluoride ions. 26–28 Our research group has reported various mesoporous composites for the adsorptive removal of fluoride, 5,9 dyes, 10–13 arsenic 8 and Cr( vi ). 14 In the present study, a mesoporous composite of cellulose has been prepared by co-precipitation of iron and aluminium in the cellulose matrix.…”
Section: Introductionmentioning
confidence: 99%